The effect of orientation, planning, action and checking (OPAC) problem-solving strategy on students' problem-solving skills and conceptual understanding - Dedel, Ernesto S., Jr. (Animo Repository, 2002)
This study focuses on the effect of Orientation, Planning, Action and Checking (OPAC) problem-solving strategy on students' problem-solving skills and conceptual understanding in teaching selected topics in mechanics.The study used the non-equivalent pretest-posttest control group design. This design consists of an experimental and control group, but subjects are not randomly assigned (quasi-experimental). Six intact classes of 153 first year college science and engineering students were used as the subjects of the study. Out of these 153 students, 69 students were in the experimental group and 84 students were in the control group. These students were enrolled in Physics 21/L (Elementary Physics I) during the second semester of school year 2001-2002 in Palawan State University. Students' achievement was measured in terms of their performance scores in a teacher-made test consisting of 20 items multiple-choice test and 5 items word problem. The 6o items mental ability test and 98 items math anxiety (MARS-A) test were also used as the instruments of the study. The results of the study are: (1) OPAC problem-solving strategy used in physics instruction significantly enhanced students' achievement in terms of (a) problem-solving skills and (b) problem-solving skills and conceptual understanding. In terms of conceptual understanding however, the effect was apparent only in the result of some specific items but not in whole the multiple-choice test. (2) Achievement in mechanics was significantly affected by students' mental ability level. (3) Students' achievement in mechanics correlated significantly but not negatively with students' math anxiety level. (4) Exposing students to explicit problem-solving strategy such as OPAC strategy reduces students' math anxiety level. (5)The problem solving styles of the expert problem solver differed significantly with that of the novice problem solver.